Risk factors associated with osteoradionecrosis. (12th January 2021) - Habib, Saad; Sassoon, Isabel; Thompson, Ian; Patel, Vinod
Abstract: Aims: Risk factors have a seminal role in ORN development. Recent technological advances such as intensity‐modulated radiation treatment (IMRT) and the rise of human papilloma virus (HPV)‐positive oropharyngeal tumours require re‐evaluation of historic risk factors and consideration of these changes. This study aims to assess potential risk factors for ORN considering recent changes in head and neck cancer (HNC). Methods: A cross‐sectional retrospective study was conducted including HNC patients who were diagnosed with ORN between 2014 and 2018. Data were collected under three main domains; patient, oncology and ORN related. The data were then grouped via tumour sub‐site and radiotherapy (RT) delivery system (IMRT vs. pre‐IMRT) for analysis. Results: A total of 197 patients were included within the cohort. Men (79.9%) and the 60–70 age bracket (39.1%) were the most populous groups. The mandible (83.2%) and posterior regions (79.9%) dominated ORN characteristics. Two thirds of ORN cases occurred from induced causes of which dental extraction (81.1%) was the main instigator. RT supplementation with surgery or chemotherapy ( p < 0.000), RT dose ( p = 0.007), primary jaw location ( p = 0.014) and secondary jaw location ( p < 0.000) were all significant variable for ORN occurrence influenced by tumour sub‐site. Comparing risk factors with the groups sub‐divided by RT delivery systems identified HPV status ( p < 0.000) as significant. Conclusion: Traditional risk factors for ORN continue to be pertinent in the modern era of HNC even with novel targeted radiation delivery systems. Additionally, HPV status should be considered as a risk factor for ORN with the increasing positive oropharyngeal group of particular concern.